(untitled) (Sciences & Technology. A, exactes sciences, 2001)
4377 pregnant ewes have been used in this study to realise a curve of lambing. This curve prove that the three most important breeds of Algerian sheep can breed all year round. To prove also that Algerian sheep are no seasonal breeder, a cytological and histological study of ewes vaginal mucosa have been done. The exfoliative cytology over all the phases of the oestrous cycle and pregnancy consistent in appearance and appear to be influenced directly by the changes in endogenous ovarian steroid hormones. The histological features of the anterior vaginal epithelium of the ewe sampled all year round, before, during, after oestrus and at pregnancy are described. In the present study, we have never found an arrest of the cyclical genital activity of ewes at any moment of the year. This finding agree with results of the curve of lambing. We can conclude that Algerian ewes are nonseasonal breeders.